Studi Analisis Aksiologi Pesantren: Eksplorasi Nilai-Nilai Etika dan Estetika Santri - Risda Mursyida; Achmad Khudori Soleh; Mohammad Nasih Al Hashas; Alfadhli (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2024)
The study of the ethical and aesthetic values ​​of Islamic boarding school students is an interesting topic to analyze from an axiological perspective, considering the close relationship between moral and ethical values ​​in their lives. This study aims to identify the ethical values ​​instilled in Islamic boarding school students and how these values ​​can be applied in their daily lives. The method used in this study is descriptive-analytical with a literature study approach, which involves collecting data from books, scientific articles, and other sources relevant to the issue of ethical and aesthetic values ​​of Islamic boarding school students in the context of axiology. The results of the study show three main points: First, the concept of axiology emphasizes that value can be interpreted as something that has utility or goodness. In philosophy, value theory is closely related to ethical and aesthetic issues. Second, related to the ethics of Islamic boarding school students, there are two main approaches, namely teleology and deontology. The teleological approach focuses on the consequences of actions; for example, if a student violates the rules of the boarding school, then he will receive consequences in the form of takzir. Meanwhile, the deontological theory emphasizes that the good or bad of a behavior is not only judged from its impact, but also from the obligation to comply with existing Islamic boarding school regulations. Third, in terms of the aesthetics of students, there are two categories, namely expressive and functional. Expressive aesthetics reflect the inner expression of an artist through works of art, such as chanting sholawat. On the other hand, functional aesthetics emphasizes that crafts or art are not only seen from the aspect of their function, but also from their beauty, such as the appearance of a clean and tidy student room.